2018
DOI: 10.1021/acsearthspacechem.8b00101
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire Burn Intensity Affects the Quantity and Speciation of Polycyclic Aromatic Hydrocarbons in Soils

Abstract: Wildfire-altered soil may be an important source of polycyclic aromatic hydrocarbons (PAHs) in the environment. With projected increase of wildfire frequency and intensity due to changing global climate, understanding the quantity and speciation of PAHs, including halogenated PAHs (XPAHs), resulting from different burn intensities has important ramifications for environmental quality concerns and global soil carbon dynamics. Here, we quantified levels of 16 U.S. Environmental Protection Agency regulated PAHs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Fire dynamics (e.g. burn temperature) and soil properties are also important features in the composition of elements within ash (Pitman 2006;Bodí et al 2014;Chen et al 2018). In general, oxides and hydroxides of Ca, Mg, Si and P particularly tend to be abundant in wildfire ash (Pereira and Ú beda 2010;Silva et al 2015) as found in the ash tested here (Supplementary material Table S1).…”
Section: Overall Ash Chemical Propertiesmentioning
confidence: 60%
See 4 more Smart Citations
“…Fire dynamics (e.g. burn temperature) and soil properties are also important features in the composition of elements within ash (Pitman 2006;Bodí et al 2014;Chen et al 2018). In general, oxides and hydroxides of Ca, Mg, Si and P particularly tend to be abundant in wildfire ash (Pereira and Ú beda 2010;Silva et al 2015) as found in the ash tested here (Supplementary material Table S1).…”
Section: Overall Ash Chemical Propertiesmentioning
confidence: 60%
“…The type of fuel and variations in combustion temperatures and oxygen availability are thought to strongly affect the concentration and type of PAHs in ash (Enell et al 2008;Rey-Salgueiro et al 2018). Chen et al (2018) found that PAHs concentrations were significantly higher in black wildfire ash (moderate burn severity) in comparison with white wildfire ash (high burn severity). This was also true of the ash types tested here with the darker (dark grey-black) ash samples (UK, URIA, CAN) containing a much higher concentration of PAHs than the lighter (light grey-white) samples (AUS, USA, SPA) (Table 4).…”
Section: Pahs Compositionmentioning
confidence: 97%
See 3 more Smart Citations